Group Mutual Exclusion Based on Priorities - Cenci, Karina M. (2011)
We propose a distributed solution for the group mutual exclusion problem based on priorities, in a network with no share memory whose members only communicate by messages. The proposed algorithm is composed by two players: groups and processes, groups are passive players while processes are active players. For the coordination access to the resource, each group has assigned a quorum. The groups have associated a base priority in each stage, meanwhile the processes have the same level priority. An important feature is that processes have associated a time to participate in the group in each stage. The message complexity obtain, in the best case, where the group does not yield the permission, is 3l + 3(q - 1) messages, where l denotes the processes linked and q denotes the quorum size. The maximum concurrency of the algorithm is n, which implies that all processes have linked to the same group.